Designing Comics By Using Problem Based Learning (PBL) to Improve Student's Creative Thinking Skills - Enny Zarvianti; Desrianti Sahida (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2020)
The designing of high school / Islamic high school physics comic teaching materials has been done to improve students' critical thinking skills in Newton's Law material. The purpose of this research is to determine to develop a physics comic for high school / Islamic high school based on problem-based learning (PBL) to improve the creative thinking skills of students at MAN Sebukar. The research method used is the research and development method, namely the 4D development method which consists of 4 phases: defining, designing, developing and disseminating. At the defining stage, need analysis on curriculum, students, and materials were carried out. The designing stage was done by designing high school / Islamic high school physics comics based on problem based learning to improve students' creative thinking skills. At the developing stage, validity, practicality and effectiveness tests were carried out. Furthermore, the disseminating stage also carried out the practicality and effectiveness tests. At the defining stage, the analysis on results of the students’ score showed the low acquisition of students competencies is due to the low creative thinking skills of students, so a teaching material is designed that is in accordance with the student's needs, materials, and learning objectives that is expected to improve students’ learning competence, namely physics comics for senior high school students/Islamic senior high school students. Furthermore, at the designing stage, an initial draft of PBL-based for / Islamic high school physics comics was made in accordance with the curriculum used in the school where the research was conducted. And in the next stage, namely the developing stage, the analysis results were obtained from the development of physics comics for high school / Islamic high school which have valid (0.85), practical (94.67%), and effective criteria for skill assessment that are judges as very good category. And the final stage after developing stage, namely the disseminating stage, researchers carried out practicality and effectiveness tests in different classes and the practicality test results were obtained in the very practical category, namely 94.33% from students’ response questionnaires and effectiveness test results from the assessment of students knowledge with a percentage of completeness reaching 82.33. % in the very good category, the students' attitude competency reached an average score of 87.43% in the very good category, the skills competency reached an average score of 89.17% with the very good category. The designing of PBL-based high school / Islamic high school physics comics is able to improve students' creative thinking skill since it eventually gives impact on students’ scores.